Moyamoya in Hispanics: not only in Japanese - Sarmad Said; Chad J. Cooper; Haider Alkhateeb; Juan M. Galvis; German T. Hernandez; Hasan J. Salameh (MDPI AG, 2014)
Moyamoya disease was first described in 1957 as hypoplasia of the bilateral internal carotid arteries, the characteristic appearance of the associated network of abnormally dilated collateral vessels on angiography was later likened to something hazy, like a puff of cigarette smoke, which, in Japanese, is moyamoya. This paper describes two cases of moyamoya presentations, including moyamoya disease and moyamoya syndrome. Moyamoya may rarely occur in North American Hispanic patients. The presentation can vary significantly and ranges bwtween fulminant outcome and prolonged survival. Awareness about moyamoya and its different presentations may be beneficial for the patients and can improve the outcome.